Kegagalan Ritel Tradisional Dalam Transformasi Digital: Studi Pada Pelaku Ritel Tradisional Di Wilayah Banjarnegara, Purbalingga, Banyumas, Cilacap, Dan Kebumen - Fitra, Joko; Reni Suci Wahyuni (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
The purpose of this study is to identify the factors contributing to the failure of traditional retail in digital transformation. This research was conducted within the grocery store trader community in five regencies: Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen. The selection of informants in this study was determined using a purposive sampling method, where 2% of the total community members in each regency were initially sampled, and data collection was stopped once data saturation was achieved. This research employed a descriptive qualitative approach, using the Miles and Huberman data analysis model, which includes data collection (observation, in-depth interviews, literature review), data reduction, data presentation, and drawing conclusions. The results of this study indicate that the forms of digital transformation undertaken by traditional retail include cashier system digitization, omnichannel integration, social media marketing, digital payments, and customer relationship management programs through member cards. The stages of digital transformation observed are initiation, adoption, adaptation, integration, and transformation. This study shows that the stages experienced by traditional retail stop at the adoption stage, as traditional retail faces limitations in knowledge, skills, social influence, and limited infrastructure support. Consequently, the subsequent stages such as adaptation, integration, and transformation cannot be continued, leading to the failure to fully realize the benefits and gain a competitive advantage.